"Every time we talk about this I feel more comfortable in overthrowing these gay-bi-hetero polarities": towards the queering of pedagogy - Couto Junior, Dilton Ribeiro (Revista Cocar, 2019)
Abstract This article, part of a recently concluded doctoral research, has the objective to question sexual identity based on the perspective of young Brazilian college students who do not identify as heterosexuals. These students constitute an online community on Facebook dedicated to questioning the regulatory norms of gender and sexuality. The theoretical framework adopted here, predominantly from studies of gender and sexuality that embrace a queer perspective, allowed me to analyse two online conversations held on Facebook with the Brazilian students. As the students contest traditional homo-bi and homo-hetero binary models, I was able to reflect on the queering of pedagogy in this article, setting the stage to reinvent the ways in which bodies, genders, and sexualities can be reimagined. Keywords: sexuality; heteronormativity; queer pedagogy. Cada vez me sinto mais confortável em derrubar essas polaridades gay-bi-hetero”: rumo à queerização da pedagogia Resumo Esse artigo, fruto de pesquisa de doutorado recentemente concluída, apresenta como objetivo questionar identidades sexuais através da perspectiva de jovens estudantes universitários brasileiros que não se reconhecem heterossexuais. Esses estudantes constituem uma comunidade online no Facebook destinada a questionar normas regulatórias de gênero e sexualidade. A fundamentação teórica adotada aqui, predominantemente dos estudos do campo de gênero e sexualidade que abarcam a perspectiva queer, permitiu analisar duas conversas online realizadas no Facebook com o grupo de estudantes brasileiros. Ao contestarem os tradicionais modelos binários homo-bi e homo-hetero, pude refletir sobre a queerização da pedagogia nesse artigo, preparando o terreno para reinventar os modos pelos quais corpos, gêneros e sexualidades podem ser reimaginados. Palavras-chave: sexualidade; heteronormatividade; pedagogia queer.